Mental and physical health, psychosocial maturity, and desistance in young adulthood - Ward, Jeffrey T. (Journal of developmental and life-course criminology, 2023)
Recent theoretical and empirical work has drawn increased attention to the role that mental and physical health can play in promoting life-course success and desistance from crime. This study integrates literature on youth development with the health-based desistance framework to investigate a key developmental pathway through which health influences desistance among system-involved youth. Using multiple waves of data from the Pathways to Desistance Study, the current study uses generalized structural equation modeling to examine whether and to what extent mental and physical health influence offending and substance use directly and indirectly through psychosocial maturity. Findings indicate that both depression and poor health stall the development of psychosocial maturity, and that those with higher psychosocial maturity are less likely to engage in offending and substance use. The model provides general support for the health-based desistance framework, finding an indirect process linking better health states to normative developmental desistance processes. Results hold important implications for the development of age-graded policies and programs geared toward promoting desistance among serious adolescent offenders both within correctional and community settings.